Reaction of a nucleoside 2, 4-dinitrophenyl phosphate with fluoride; a convenient method for the preparation of the nucleoside phosphorfluoridate. - Johnson, P W (1975)
Examination of the reaction of 2, 4-dinitrofluorobenzene with thymidine-5' phosphate in detail reveals that the initial product is the 2, 4-dinitrophenyl ester. This reacts with fluoride to produce thymidine-5' phosphorfluoridate. This second reaction provides the basis for the conversion of preformed thymidine-5' 2, 4-dinitrophenyl phosphate to thymidine-5' phosphorofluoridate.